2006
DOI: 10.1002/jor.20228
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of endothelial precursor cells: Systemic vascular response to musculoskeletal trauma

Abstract: Postnatal vasculogenesis, the process by which vascular committed bone marrow stem cells or endothelial precursor cells (EPC) migrate, differentiate, and incorporate into the nacent endothelium contributing to physiological and pathological neovascularization, has stimulated much interest. Its contribution to tumor nonvascularization, wound healing, and revascularization associated with skeletal and cardiac muscles ischaemia is established. We evaluated the mobilization of EPCs in response to musculoskeletal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…While the higher vasculogenic potential of UCB-derived ECFC is largely expected, the higher expression of osteogenesis-related genes here may reflect the intense skeletal development occurring during neonatal life as compared to the mature adult. These circulating ECFC are found at higher frequencies during neonatal life compared to adult life [46], with increased mobilization in the event of bony injury [47,48].…”
Section: Discussionmentioning
confidence: 97%
“…While the higher vasculogenic potential of UCB-derived ECFC is largely expected, the higher expression of osteogenesis-related genes here may reflect the intense skeletal development occurring during neonatal life as compared to the mature adult. These circulating ECFC are found at higher frequencies during neonatal life compared to adult life [46], with increased mobilization in the event of bony injury [47,48].…”
Section: Discussionmentioning
confidence: 97%
“…We found the largest increase in EPCs at Day 7, which may indicate the true peak of EPC mobilization in our model was at an earlier time point. Increased endothelial precursor cells have also been observed after closed tibial fracture in patients [32]. Wang et al [57] reported a doubling in circulating HSCs at 7 days after creation of a calvarial defect in C57BL/6 male mice and this number was further increased when AMD3100 was administered.…”
Section: Discussionmentioning
confidence: 98%
“…This new paradigm uses pharmacologic induction of mobilization and endogenous mechanisms of cell homing and engraftment to sites of injury. It is plausible this strategy simply mimics and amplifies normal repair mechanisms as progenitor cells are mobilized to the PB after stroke [41], vascular trauma [20], musculoskeletal trauma [31,32], fracture [3,34], distraction osteogenesis [34], and myocardial infarction [60]. An important pathway for stem cell mobilization is the SDF-1/CXCR4 axis and there are recent data supporting the concept that transient disruption of this receptor-ligand complex through the CXCR4 antagonist, AMD3100, enhances bone formation in vivo [57,59].…”
Section: Discussionmentioning
confidence: 99%
“…22 There seem to be several distinct cell populations capable of giving rise to osteoblasts, 6,11,23 with CD34 expression as the only shared characteristic. In fracture patients, circulating non-adherent CD34+ preosteoblasts, 11 and fibronectin adherent CD34+ cells 23 have been found at elevated numbers. Also osteogenic differentiation of circulating EPCs has been demonstrated, and PB derived CD34+ cells have been shown to recruit to fracture sites when systemically injected in a rat model.…”
Section: Discussionmentioning
confidence: 99%